2013
DOI: 10.1016/j.engstruct.2013.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic behavior of thin RC Peruvian shear walls: Full-scale experimental investigation and numerical simulation

Abstract: The experimental results of seven full-scale thin RC shear walls subjected to cycling loading are presented. The objective of these experiments is to evaluate the use of electro-welded wire mesh as the main reinforcement instead of a conventional reinforcement. Six walls are equipped with the electro-welded wire mesh, which is made of a non-ductile material, and one wall is reinforced with conventional bars, which are made of a ductile material. A single layer of main reinforcement is used in both directions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 8 publications
3
13
0
5
Order By: Relevance
“…The three-parametric model proposed by Park et al [7], based on a trilinear curve, was adopted. The four parameters α, β 1 , β 2 , and γwere estimated in the previous study [3].…”
Section: Archetypal Structure and Numerical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The three-parametric model proposed by Park et al [7], based on a trilinear curve, was adopted. The four parameters α, β 1 , β 2 , and γwere estimated in the previous study [3].…”
Section: Archetypal Structure and Numerical Modelmentioning
confidence: 99%
“…This study assesses the seismic performance of thin RC wall high-rise buildings in Lima, Peru, using fragility functions. We evaluated the hysteretic response of thin RC walls in a previous study [3]. Multiple degree-offreedom and macro models representing the overall behavior of RC elements were used to construct numerical model of high-rise buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Those research achievements provide reliable test data for the application of this shear wall in multi-story building structures which meet the basic seismic demand as the Code for Seismic design of Building (GB50011, 2010) required. The thin shear walls reinforced with single layer of deformed bars and welded-wire mesh are also used for one-totwo stories housing in several Latin American countries (Carrillo et al, 2015;Quiroz et al, 2013). Focusing on the function of inclined steel bars in seismic performance for shear walls (Salonikios et al, 1999(Salonikios et al, , 2000(Salonikios et al, , 2007, some results about static testing of single layer of web reinforcement and inclined steel bars (Zhang et al, 2016a(Zhang et al, , 2016d(Zhang et al, , 2017 have indicated that inclined steel bars can improve the hysteretic response of shear walls with single layer of web reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Nie et al [15] studied the seismic behavior of high-strength concrete filled double-steel-plate composite walls under the large axial compressive force and reversed cyclic lateral load, and analyzed the stiffness, strength degradations, and deformation characteristics. In 2013, Quiroz et al [16] studied the cyclic behavior of thin RC Peruvian shear walls through full-scale experimental investigation and numerical simulation.…”
Section: Introductionmentioning
confidence: 99%